Influence of Infrared Thermography Predictors in Dental Implant Osteotomies: An Ex Vivo Study - Barriga-Yauri, Gabriel; Alvitez-Temoche, Daniel Augusto; Mauricio, Franco; Espinoza-Carhuancho, Fran; Calderon, Ivan; Medina, Julia; Mayta-Tovalino, Frank (My University, 2025)
Objective: To evaluated the contribution of irrigation, drill type, motor, and dental implant system on infrared thermographic variations in osteotomies. Methods: Osteotomy sites for 240 implants were prepared with three implant systems (Arcys, NeoBiotech and Osstem), with 80 samples analyzed in each group. Each group was further subdivided according to the drilling conditions (with and without irrigation) and motor type (Coxo, W&H, Dentflex, Driller). The drill sequence included baseline, pilot, second and third drills at 1200 rpm and 40 Ncm. Infrared thermographic measurements were performed using a Fluke TiS55+ camera, with a resolution of 220 × 165 pixels and a temperature range of −20 °C to 450 °C. Statistical analysis consisted of ANOVA with Bonferroni post hoc test and linear regression model, with a view to evaluate the influence of the variables on final temperature changes. Results: Irrigation caused a much lower temperature across all implant systems (P < .001). When not irrigated, Arcys showed the highest temperatures, while in both NeoBiotech and Osstem the heat dissipated better. The Bonferroni post hoc test revealed no significant temperature difference existed among implant systems without irrigation. With irrigation, however, Arcys had a higher temperature than NeoBiotech and Osstem (P < .001). The type of motor had no statistically significant influence on the temperature of the final drilling (P > .05). Based on the regression analysis, the baseline, pilot, and second drill temperatures were the strongest predictors of the final drill temperature, with irrigation influencing the effects of the drill temperature. Conclusion: Irrigation decreased the thermal stress during osteotomy, while NeoBiotech and Osstem showed better heat dispersing abilities. The motor type does not have a significant influence on the temperature differences. These findings establish the basic need for effective irrigation protocols to avoid thermal osteodisruption and promote osseointegration in implantology.
Keywords: Dental implant; Ex vivo study; Infrared; Thermographic alterations; https://purl.org/pe-repo/ocde/ford#3.02.14